(untitled) (Journal of Telenursing (JOTING), 2023)
This study aims to analyze the relationship between nurse performance and patient satisfaction at RSU. Royal Prima Medan. This research method is correlation research with a quantitative approach. The sample of this study was inpatients, namely as many as 99 respondents using a convenience sampling technique. Data collection using a questionnaire. Data analysis used Spearman rank statistical test analysis. The results showed that there was a relationship between nurse performance and patient satisfaction p = 0.000 (p <0.05). Based on Spearman’s rank correlation coefficient for nurse performance with patient satisfaction obtained by 0.525 means there is a moderate and unidirectional relationship between the two variables. The better the nurse’s work performance, the patient’s satisfaction will also increase. In conclusion, there is a relationship between nurse performance and patient satisfaction at RSU. Royal Prima Medan. Keywords : Job Performance, Nurse, Patient Satisfaction.